Efektivitas Penyuluhan Terhadap Pengetahuan Tentang Teknik Akupresur untuk Meningkatkan Konsentrasi pada Siswa di SMKN 1 Tembuku - Rastiti, Ida Ayu Anom; Strisanti, Ida Ayu Suptika; Bhandesa, Asthadi Mahendra (Jayapangus Press, 2024)
Student academic achievement is one of the main indicators used to assess the quality of education. One of the reasons for the low student learning outcomes currently is the lack of student concentration during the learning process. Concentration is the initial aspect of processing information. As for improving learning achievement, students should increase their concentration during the learning process. Acupressure is a therapeutic modality that has been proven to have the function of improving an individual's cognitive abilities. Many studies have found that acupuncture points, which can also be used for acupressure, have the effect of improving cognitive abilities. On this basis, researchers conducted a study related to the effect of health education on students' level of knowledge about acupressure to increase concentration in students at SMKN 1 Tembuku. Respondents were asked to fill out pre-test and post-test questionnaires before and after counseling to measure changes in knowledge. The results showed a significant increase in knowledge scores before and after the extension activities. Knowledge scores about acupressure increased from before (Md = 5.00) to (Md = 9.50) after counseling with a p-value < 0.01. This is also supported by the attitudes of respondents where the majority of respondents stated that they would apply this technique to increase study concentration. Participants' knowledge regarding acupressure to improve concentration have increased after receiving health education. Increasing the knowledge of respondents regarding acupressure techniques is a very good thing. This is because the acupressure technique has a number of benefits in increasing brain development and stimulating the secretion of neurotransmitters and hormones which are important for increasing student concentration. The acupressure technique is easy to use and has no side effects and can be applied by participants independently. Therefore, increasing knowledge of acupressure is very beneficial for school students, especially for those who often experience decreased concentration in studying.